2020
DOI: 10.3390/cancers12061542
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Extracellular Traps (NETs) Promote Pro-Metastatic Phenotype in Human Breast Cancer Cells through Epithelial–Mesenchymal Transition

Abstract: Neutrophil extracellular traps (NETs) have been associated with several steps of tumor progression, including primary growth and metastasis. One of the key features for the acquisition of the metastatic ability is the epithelial–mesenchymal transition (EMT), a complex cellular program. In this study, we evaluated the ability of isolated NETs in modulating the pro-metastatic phenotype of human breast cancer cells. Tumor cells were treated with isolated NETs and then samples were generated for cell migration, qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
88
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(110 citation statements)
references
References 75 publications
6
88
0
2
Order By: Relevance
“…Next, we examined the mechanism by which NETs could activate the EGFR pathway. It has been shown that various kinds of cytokines are secreted in the formation of NETs which maybe induce the invasive and migratory abilities of pancreatic cancer cells, such as IL‐6, IL‐1β, IL‐1A, IL‐7A, IL‐17A, IL‐4, IL‐11, IL‐33, IL‐17F, IL‐37, TGF‐α TNF, IL‐23, IL‐10, IL‐36, IL‐29 and IL‐14 16,36‐40 . Real‐time PCR results showed that IL‐1β, IL‐6, IL‐8, IL‐10 and IL‐36 mRNA levels were significantly upregulated in NETs and downregulated when the formation of NETs was inhibited (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we examined the mechanism by which NETs could activate the EGFR pathway. It has been shown that various kinds of cytokines are secreted in the formation of NETs which maybe induce the invasive and migratory abilities of pancreatic cancer cells, such as IL‐6, IL‐1β, IL‐1A, IL‐7A, IL‐17A, IL‐4, IL‐11, IL‐33, IL‐17F, IL‐37, TGF‐α TNF, IL‐23, IL‐10, IL‐36, IL‐29 and IL‐14 16,36‐40 . Real‐time PCR results showed that IL‐1β, IL‐6, IL‐8, IL‐10 and IL‐36 mRNA levels were significantly upregulated in NETs and downregulated when the formation of NETs was inhibited (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…NETs also act as a drug target to counteract chronic and acute inflammation 15 . It has also been reported that NETs could promote EMT 16 and enhance metastasis through CCDC25 17 in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that a likely target for proteases is the adhesion molecule expressed on the surface of HCC cells. 31 , 41 , 43 In order to test this hypothesis, HCC cell layers were incubated with NETs-CM for up to 20 h; then, the depleted area of HCC cells was quantified. We observed that incubation with NETs-CM resulted in significant dyshesion of the HCC cell layers ( Figure 9C ).…”
Section: Resultsmentioning
confidence: 99%
“…Since NETosis is toxic in the lung (4, 6) and it induces the EMT in breast cancer cells (9), we investigated if NETs can induce the EMT in the alveolar epithelial cell line A549. We used PMA as a primary chemical effector of NETosis.…”
Section: Resultsmentioning
confidence: 99%
“…The direct consequence of NETs persistence in the lung is the damage of epithelial and endothelial cells, driven predominantly by histones (1). Additionally, NETs have been found to drive the EMT in the context of the breast cancer thanks to their capacity to upregulate transcription factors involved in the EMT (ZEB1 and SNAI1) (9). Given these premises, the aim of this study is to assess whether NETosis may drive the EMT also in lung epithelial cells.…”
Section: Introductionmentioning
confidence: 99%